Anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film and preparation thereof
By using anodized aluminum/polyvinylidene fluoride trifluoroethylene film to form an electroactive Janus composite film, the problem that existing materials are difficult to meet multiple performance requirements for bone repair at the same time is solved, and effective repair and regeneration of bone tissue is achieved.
Patent Information
- Application Number
- CN202411718458.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Existing materials are difficult to meet the structural bionic, mechanical and electrical properties requirements of bone repair at the same time, resulting in poor bone tissue repair and regeneration effects.
Anodic aluminum/polyvinylidene fluoride trifluoroethylene film is used to form a Janus film by heating and polarization, and an electroactive Janus composite film is formed. The film has asymmetric structure and properties, which can simulate the extracellular matrix structure and electrical microenvironment of bone tissue.
The electrical microenvironment simulation of bone tissue is realized, which induces cell proliferation and differentiation, promotes bone tissue repair and regeneration, and has a regulated surface potential, which is suitable for different application scenarios.
Smart Images

Figure HDA0005157436870000011 
Figure HDA0005157436870000012 
Figure HDA0005157436870000013
Abstract
Description
Technical Field
[0001] The invention relates to the biomedical field, and in particular to an anodic aluminum oxide / polyvinylidene fluoride trifluoroethylene film and a preparation method thereof. Background Art
[0002] Bone is a histological structure responsible for movement, protection, and maintenance of mineral balance in the body and support of human structure, with unique mechanical, electrical and other properties. Bone physiology includes many complex biological processes. After bone injury, a series of biochemical changes and molecular signal reactions will occur at the injured site, forming a microenvironment that is not conducive to bone repair, amplifying the negative effects of inflammation, and inducing cell apoptosis.
[0003] In situ tissue engineering refers to the use of bone regeneration potential to recruit endogenous stem cells to the site of bone damage to achieve the effect of enhancing bone repair. In situ bone tissue engineering often uses a certain method to modify materials and construct a natural bone regeneration microenvironment to improve cell survival and proliferation, induce directional differentiation, etc., and ultimately achieve reconstruction and permanent replacement of the defect site. Among them, the surface of the material will contact and interact with the cells, which will have an important impact on bone repair. The physical, chemical and structural properties of the material surface are considered to be closely related to cell behavior and can act on cells alone or together.
[0004] The structure of a material affects its performance. The surface topology of a material is an important factor affecting its surface performance, and it also has an important impact on protein adsorption and cell behavior. The topological structure of a material surface can be considered as a hierarchical structure, that is, from the atomic and molecular structures that make up the material, to micrometer and nanostructures in a certain aggregation state, and then to the overall macroscopic structure. Common topological structures include patterning, porous structures, roughness, etc. On the one hand, the surface topological structure will have a significant effect on protein adsorption. On the other hand, cells will respond to the micro-nano topological structure of the material surface. Existing studies have shown that micro-nano structures play an important regulatory role in cell behavior, including cell adhesion, spreading, migration, proliferation, and differentiation.
[0005] Cell behavior is not only affected by structure, but also closely related to the electrical microenvironment. Endogenous electric fields exist in various tissues in the human body, participating in various physiological activities of cells and tissues. Bone tissue has a specific physiological potential, and after damage, a damage potential will appear, which is not conducive to bone repair. By simulating the electrical microenvironment of bone repair, cells from surrounding tissues can be recruited to promote tissue repair and regeneration.
[0006] However, most existing materials can only achieve a certain microenvironment simulation and it is difficult to meet multiple performance requirements at the same time. Therefore, developing a material that can simultaneously meet the requirements of structural bionics, mechanical and electrical properties is of great significance for tissue repair and regeneration. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide an anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film as an electroactive Janus composite film that can simultaneously simulate the structure and electrical microenvironment of bone repair, regulate cell behavior, and promote tissue repair and regeneration. In addition, the film of the present invention also has an adjustable surface potential and can be applied to different application scenarios.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] The invention provides an anodic aluminum oxide / polyvinylidene fluoride trifluoroethylene film, which is composed of an upper polyvinylidene fluoride trifluoroethylene film layer subjected to polarization treatment and a lower anodic aluminum oxide film layer.
[0010] In some specific examples of the present invention, the polyvinylidene fluoride trifluoroethylene film layer is a β-phase PVTF crystal.
[0011] In some specific examples of the present invention, the anodized aluminum oxide film layer is amorphous AAO.
[0012] In some specific examples of the present invention, the piezoelectric coefficient d of the anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film is 33 Satisfy: -20pC / N≤d 33 <0pC / N or 0pC / N<d 33 ≤20pC / N.
[0013] At the same time, the present invention also provides a method for preparing the above-mentioned anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film, comprising the following steps:
[0014] S1, mixing polyvinylidene fluoride trifluoroethylene powder and N,N-dimethylformamide and stirring to obtain a solution, dropping the solution on a substrate, using a film applicator to evenly disperse the solution on the substrate to form a film, and annealing to obtain a PVTF film on the substrate;
[0015] S2, stacking the PVTF film on an anodized aluminum template, placing it on a hot plate for heating and keeping it warm for a period of time, and then cooling it naturally with the hot plate to obtain a Janus film;
[0016] S3. performing polarization treatment on the Janus film.
[0017] In some specific examples of the present invention, in step S1, the feed ratio of polyvinylidene fluoride trifluoroethylene powder to N,N-dimethylformamide is 1 g: (6-12) ml, preferably 1 g: 6 ml.
[0018] In some specific examples of the present invention, in step S1, the substrate is a glass plate, preferably a tempered glass plate.
[0019] In some specific examples of the present invention, in the step S1, the height of the applicator is set to 60-90 μm, preferably 70 μm.
[0020] In some specific examples of the present invention, in step S1, the temperature of the annealing treatment is 180-220°C, preferably 210°C.
[0021] In some specific examples of the present invention, in step S1, the annealing treatment time is 0.5 to 2 hours, preferably 1 hour.
[0022] In some specific examples of the present invention, in step S1, the film thickness of the PVTF film is 50-90 μm, preferably 55 μm.
[0023] In some specific examples of the present invention, in step S2, the pore size of the anodized aluminum template is 20 to 500 nm.
[0024] In some specific examples of the present invention, in step S2, the heating temperature on the hot plate is 160-220°C, preferably 160°C.
[0025] In some specific examples of the present invention, in step S2, the heat preservation time on the hot plate is 5 to 60 minutes, preferably 10 minutes.
[0026] In some specific examples of the present invention, in step S3, the polarization treatment adopts a corona polarization method.
[0027] In some specific examples of the present invention, in step S3, the piezoelectric coefficient d of the target product obtained by the polarization treatment is 33 Satisfy: -20pC / N≤d 33 <0pC / N or 0pC / N<d 33 ≤20pC / N.
[0028] In some specific examples of the present invention, in step S3, the voltage of the high voltage electric field of the polarization treatment is 10-15 kV, and the time of the polarization treatment is 60-80 min.
[0029] In some specific examples of the present invention, in step S3, the voltage of the high voltage electric field of the polarization treatment is 10 kV, and the time of the polarization treatment is 60 min.
[0030] In the present invention, anodized aluminum and polyvinylidene fluoride trifluoroethylene film are composited by heating to form a Janus film (Janus film refers to a film material with asymmetric morphology or chemical composition on both sides of the film), and then polarized to obtain an electroactive Janus film.
[0031] Compared with the prior art, the present invention has the following beneficial technical effects:
[0032] (1) The anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film of the present invention is an electroactive Janus film. The two sides of the film have asymmetric structures and properties, which can simulate the bionic porous structure of the extracellular matrix (ECM) structural microenvironment in bone tissue, and have excellent electroactivity and surface electrical signals, which can simulate the electrical microenvironment of bone tissue and induce cell proliferation and differentiation. Moreover, the biologically inert AAO can help isolate different tissues, prevent adhesion while promoting tissue repair, and the electroactive polarized PVTF is more affinity with cells and more conducive to cell proliferation. The membrane layers of the electroactive Janus membrane are tightly bonded. When used as a biomedical implant, it can simultaneously construct a structural bionic microenvironment and an electrical bionic microenvironment, and use the synergistic effect of electrical signals and topological structures to regulate cell behavior, promote cell growth and bone tissue repair and regeneration.
[0033] (2) The process of the present invention is simple and low in cost, and the performance of the target product can be regulated by changing the specific parameters of heating and polarization. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The XRD patterns are obtained by X-ray diffraction characterization of the anodized aluminum film used in Example 1 and the PVTF film obtained in step (1).
[0035] Figure 2 This is the Fourier transform infrared spectrum test result of the PVTF side of the target product obtained in Example 1.
[0036] Figure 3A This is the contact angle test result of the target product AAO side obtained in Example 1.
[0037] Figure 3B This is the contact angle test result of the composite film PVTF side obtained in step (2) in Example 1.
[0038] Figure 3C This is the contact angle test result of the PVTF side of the target product obtained in Example 1.
[0039] Figure 4A This is a SEM image of the surface morphology of the target product AAO side obtained in Example 1.
[0040] Figure 4BThis is a SEM image of the cross-sectional morphology (part) of the target product AAO side obtained in Example 1.
[0041] Figure 4C This is a SEM image of the surface morphology of the target product PVTF side obtained in Example 1.
[0042] Figure 5A This is a SEM image of the morphology of a certain area of the target product obtained in Example 1.
[0043] Figure 5B The target product obtained in Example 1 Figure 5A EDS scan results of the area shown.
[0044] Figure 6 This is a SEM image of the surface morphology of the product obtained in Comparative Example 1.
[0045] Fig. 7A The figure shows the situation after one day of cell culture on the sample surface on the AAO side of the target product obtained in Example 1.
[0046] Figure 7B The figure shows the cells after one day of culture on the sample surface on the PVTF side of the Janus membrane obtained in step (2).
[0047] Figure 7C The figure shows the situation after one day of cell culture on the sample surface on the PVTF side of the target product obtained in Example 1.
[0048] Fig.7D The figure shows the state of cells after being cultured on the sample surface on the PVTF side of the target product obtained in Example 1 for three days. DETAILED DESCRIPTION
[0049] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is subject to the claims.
[0050] In the following examples, the reagents or instruments used without indicating the manufacturer are all conventional products available on the market. For example, the glass plate is a tempered glass plate, and the vinylidene fluoride-trifluoroethylene copolymer (i.e., polyvinylidene fluoride-trifluoroethylene Poly (VDF-TrFE), P (VDF-TrFE), abbreviated as PVTF) is produced by Piezotech, France, and the model is: FC30, wherein the molar ratio of vinylidene fluoride monomer to trifluoroethylene monomer is 7:3. The anodized aluminum template uses an AAO membrane with a pore size of 0.1um, the brand is GE Whatman, and the model is 6809-7013-Whatman aluminum oxide membrane.
[0051] The corona polarization device includes: a high-voltage DC power supply and a round-head electrode needle. The round-head electrode needle is placed 1 cm above the sample and connected to the positive and negative electrodes of the power supply with the negative plate below the sample. The voltage is gradually increased to reach the critical voltage (polarization voltage) to perform corona discharge and maintain for a certain time.
[0052] Example 1
[0053] (1) 1 g of PVTF powder was mixed with 6 ml of N,N-dimethylformamide (DMF) and magnetically stirred for 6 h to obtain a PVTF solution; the PVTF solution was dropped onto a glass plate and uniformly dispersed by an applicator to form a film. The applicator height was set to 70 μm, and the solution was annealed and crystallized in a muffle furnace at 210°C for 1 h to obtain a PVTF film with a film thickness of 55 μm;
[0054] (2) washing the PVTF film with deionized water and ethanol and drying it, and washing the anodized aluminum template with deionized water and ethanol and drying it; then, stacking the PVTF film peeled off from the glass plate on the anodized aluminum template (i.e., placing the PVTF film on the anodized aluminum template), placing it on a hot plate and heating it to 160° C., keeping it warm for 10 minutes, and then cooling it naturally with the hot plate to obtain a Janus film;
[0055] (3) The Janus membrane obtained in step (2) is polarized by corona polarization, the voltage of the high-voltage electric field of the polarization treatment is 10 kV, and the polarization treatment time is 60 min to obtain the target product.
[0056] Performance and testing:
[0057] The PVTF film obtained in step (1) of this embodiment 1 and the anodized aluminum film used were characterized by X-ray diffraction, and the corresponding XRD patterns are shown in FIG. Figure 1 shown. Figure 1 In the XRD spectrum of AAO, the diffraction peaks at 20.7° and 38.0° correspond to the (200) and (001) reflections of the PVTF β phase, indicating that the PVTF film obtained in step (1) is a β-phase PVTF crystal; while the XRD spectrum of AAO shows a bun peak at 20° to 30°, corresponding to the diffraction peak of amorphous Al2O3, indicating that AAO is amorphous.
[0058] The PVTF side of the target product obtained in Example 1 was analyzed by Fourier transform infrared spectroscopy, and its FTIR graph is as follows: Figure 2 shown. Figure 2 In 840cm -1 、1285cm -1 and 1400cm -1 The characteristic β phase band of PVTF is shown at , indicating that PVTF is β phase. In the target product obtained in Example 1, AAO is still amorphous.
[0059] The target product obtained in Example 1 was subjected to EDS analysis. The morphology of the EDS scanning area and the EDS scanning results were as follows: Figure 5A and Figure 5B As shown, the upper part of the image is mainly composed of three elements: F, O, and C, which should be PVTF; the main elements of the lower part are Al and O, which should be AAO. It can be seen that in the target product, AAO and PVTF are tightly combined without other impurities.
[0060] The contact angles of the AAO side of the target product in Example 1, the PVTF side of the Janus film obtained in step (2), and the PVTF side of the target product were tested, and the results were as follows: Figure 3A to Figure 3C As shown, the contact angles are 26.1°, 86.8° and 41.7°, respectively, which indicates that: ① both sides of the target product are hydrophilic, and the hydrophilicity of the AAO side is better than that of the PVTF side; ② the hydrophilicity of the PVTF side is significantly improved after polarization treatment.
[0061] The surface morphology and cross-sectional morphology of the AAO side of the target product obtained in Example 1 were observed using a scanning electron microscope. The SEM images are as follows: Figure 4A and Figure 4B The PVTF side of the target product of Example 1 was observed using a scanning electron microscope. Figure 4C shown.
[0062] Figure 4A In the figure, the surface morphology of the AAO side of the target product is a nanopore array structure, the pore sizes are basically the same, the pores are uniform and orderly, and the pore diameter is 200nm; Figure 4B In the figure, the cross-sectional morphology of the AAO side of the target product is nanopores arranged parallel to each other, perpendicular to the alumina surface and substrate; Figure 4C In the figure, the surface morphology of the PVTF side of the target product shows a typical wrinkled morphology after PVTF annealing and crystallization. It can be seen that the two sides of the target product show different surface morphologies.
[0063] The composite film obtained in step (2) was measured using a static piezoelectric coefficient D33 measuring instrument, showing that its surface piezoelectric coefficient d33 was 0 pC / N; the target product was measured using a static piezoelectric coefficient D33 measuring instrument, showing that the surface piezoelectric coefficient d33 of the target product was -15 pC / N. This shows that corona poling can improve the piezoelectric properties of the target product and the target product is electrically active.
[0064] In summary, the target product obtained in Example 1 is an anodic aluminum oxide / polyvinylidene fluoride trifluoroethylene composite film, which is an electroactive Janus composite film with asymmetric chemical composition and properties on both sides.
[0065] Cell experiments
[0066] After the cryopreserved rat bone marrow mesenchymal stem cells (MSCs) were revived, they were cultured in DMEM low-glucose medium for 3 days, then digested with trypsin, resuspended, and prepared into a cell suspension. The cell suspension was inoculated on the surface of a sample with a size of 1cm×1cm in each well of a 24-well plate, and then placed in a constant temperature and humidity incubator at a temperature of 37°C and a carbon dioxide concentration of 5%. Fresh DMEM low-glucose medium was replaced every other day. After a period of culture, the samples were taken out for the following treatments: the culture medium was aspirated, 4% paraformaldehyde was added to fix at room temperature for 15 minutes, the paraformaldehyde was aspirated, washed with PBS twice, and then dehydrated with ethanol gradient: soaked in 500ul of ethanol with a volume concentration of 30%, 50%, 75%, 90%, and 95%, respectively, soaked in each concentration for 15 minutes, aspirated the ethanol, and finally added 200ul of cell swelling agent (hexamethyldisilazane), aspirated after 10 minutes, and the samples were stored in a drying dish. The surface of the samples was observed by scanning electron microscopy. The results are as follows FIG. 7A to FIG. 7D shown.
[0067] The sample surfaces are respectively the AAO side of the target product obtained in Example 1, the PVTF side (unpolarized) of the Janus membrane obtained in step (2), and the PVTF (polarized) side of the target product obtained in Example 1. The surface conditions of the samples after one day of cultivation are as follows: Figure 7A to Figure 7C As shown. In terms of density, the cell density on the AAO side of the target product obtained in Example 1 and the PVTF side of the target product obtained in Example 1 is greater than the cell density on the PVTF side of the Janus membrane obtained in step (2), indicating that the materials on both sides of the target product obtained in Example 1 are more conducive to cell adhesion; in terms of cell morphology and size, the cells on the PVTF side of the Janus membrane obtained in step (2) are less spread and have a smaller area, while the cells on the AAO side of the target product obtained in Example 1 and the PVTF side of the target product are more spread and have a larger area, especially the cells on the PVTF side of the target product obtained in Example 1 have the largest spread and the largest area, indicating that the cells are more affinity with the PVTF side of the target product obtained in Example 1.
[0068] Furthermore, the surface condition of the PVTF side of the target product obtained in Example 1 after three days of culture was observed. Fig.7D As shown, it can be found that: compared with the situation of one day of culture, the cell density and area increased after three days of culture, indicating that the PVTF side of the target product obtained in Example 1 is conducive to cell proliferation; at the same time, it can be observed that the cells are in contact with each other and form a large area of spreading, indicating that the cells are in good growth state.
[0069] It can be seen that the target product AAO side and PVTF side have different regulatory control effects on cell adhesion and proliferation, and will have different effects on cell behavior.
[0070] Example 2
[0071] (1) 1 g of PVTF powder was mixed with 6 ml of N,N-dimethylformamide (DMF) and magnetically stirred for 6 h to obtain a PVTF solution; the PVTF solution was dropped onto a glass plate and uniformly dispersed by an applicator to form a film. The applicator height was set to 70 μm, and the solution was annealed and crystallized in a muffle furnace at 210°C for 1 h to obtain a PVTF film with a film thickness of 55 μm;
[0072] (2) washing the PVTF film with deionized water and ethanol and drying it, and washing the anodized aluminum template with deionized water and ethanol and drying it; then, stacking the PVTF film peeled off from the glass plate on the anodized aluminum template (i.e., placing the PVTF film on the anodized aluminum template), placing it on a hot plate and heating it to 160° C., keeping it warm for 10 minutes, and then cooling it naturally with the hot plate to obtain a Janus film;
[0073] (3) The Janus membrane obtained in step (2) is polarized by corona polarization, the voltage of the high-voltage electric field of the polarization treatment is 15 kV, and the polarization treatment time is 60 min to obtain the target product.
[0074] The static piezoelectric coefficient of the target product obtained in this example was measured, and its static piezoelectric coefficient was -20 pC / N. This shows that the electrical activity can be regulated by adjusting the polarization parameters.
[0075] Comparative Example 1
[0076] (1) 1 g of PVTF powder was mixed with 18 ml of N,N-dimethylformamide (DMF) and magnetically stirred for 6 h to obtain a PVTF solution; a PVTF film was prepared by spin coating with a film thickness of about 3 μm;
[0077] Spin coating method: Use a glass sheet as the substrate, place it on a sheet holder, use a vacuum pump to evacuate, fix the glass sheet under negative pressure, drop the prepared PVTF solution to the center of the substrate, and rotate the substrate so that the solution is evenly covered on the substrate surface under the action of centrifugal force. Instrument for spin coating: KW-4A desktop glue machine.
[0078] (2) Separating the PVTF film from the glass sheet with deionized water, and cleaning the anodized aluminum template with deionized water and ethanol in turn and drying it; then, stacking the separated PVTF film on the anodized aluminum template (i.e., placing the PVTF film on the anodized aluminum template), placing it on a hot plate and heating it to 200°C, keeping it warm for 30 minutes, and then cooling it naturally with the hot plate to obtain a composite film.
[0079] (3) polarizing the composite film obtained in step (2) by corona polarization method,
[0080] The composite film obtained in this comparative example 1 was observed using a scanning electron microscope. Figure 6 As shown in the figure, a hole structure appeared on the PVTF side, indicating that the PVTF thickness was insufficient and could not achieve complete coverage.
[0081] In summary, the target product obtained by the present invention is an electroactive Janus membrane, and the two sides of the film have asymmetric properties and structures, including wettability, conductivity and chemical activity. One side is anodized aluminum, which has a bionic porous structure, can simulate the extracellular matrix (ECM) structural microenvironment in bone tissue, and provide a suitable structural microenvironment for osteoblasts. Moreover, the biologically inert AAO can help isolate different tissues and prevent adhesion while promoting tissue repair; one side is a PVTF film layer, which is electrically active after polarization treatment. The piezoelectric effect of PVTF can be used to simulate the electrical microenvironment of bone tissue and induce cell proliferation and differentiation; and by adjusting the polarization parameters, target products with different static piezoelectric coefficients can be obtained. The Janus membrane is well combined and has a certain structural strength due to the positive aluminum oxide template. Therefore, the electroactive Janus anodized aluminum / polyvinylidene fluoride film of the present invention can simultaneously construct a structural bionic microenvironment and an electrical bionic microenvironment, and use the synergistic effect of electrical signals and topological structures to regulate cell behavior and promote bone tissue repair and regeneration. The preparation method of the present invention is simple in process and low in cost.
[0082] It can be seen that the purpose of the present invention has been completely and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments. Without departing from the principles, the implementation methods can be modified arbitrarily. Therefore, the present invention includes all modified implementation methods based on the spirit and scope of the claims.
Claims
1. An anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film, characterized in that: It consists of an upper layer of a polarized polyvinylidene fluoride trifluoroethylene film layer and a lower layer of an anodized aluminum film layer.
2. The anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to claim 1, characterized in that: The polyvinylidene fluoride trifluoroethylene film layer is a β-phase PVTF crystal.
3. The anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to claim 1, characterized in that: The anodized aluminum film layer is amorphous AAO.
4. The anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to claim 1, characterized in that: Its piezoelectric coefficient d 33 Satisfy: -20pC / N≤d 33 <0pC / N or 0pC / N<d 33 ≤20pC / N.
5. The method for preparing anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to any one of claims 1 to 4, comprising the following steps: S1, mixing polyvinylidene fluoride trifluoroethylene powder and N,N-dimethylformamide and stirring to obtain a solution, dropping the solution on a substrate, using a film applicator to evenly disperse the solution on the substrate to form a film, and annealing to obtain a PVTF film on the substrate; S2, stacking the PVTF film on an anodized aluminum template, placing it on a hot plate for heating and keeping it warm for a period of time, and then cooling it naturally with the hot plate to obtain a Janus film; S3. performing polarization treatment on the Janus film.
6. The method for preparing anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to claim 5, characterized in that: In the step S1, the feed ratio of polyvinylidene fluoride trifluoroethylene powder to N,N-dimethylformamide is 1 g: (6-12) ml.
7. The method for preparing anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to claim 5, characterized in that: In the step S1, the temperature of the annealing treatment is 180-220° C., and the time of the annealing treatment is 0.5-2 hours.
8. The method for preparing anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to claim 5, characterized in that: In the step S2, the pore size of the anodized aluminum template is 20 to 500 nm.
9. The method for preparing anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to claim 5, characterized in that: In the step S2, the heating temperature on the hot plate is 160-220° C., and the heat preservation time on the hot plate is 5-60 minutes.
10. The method for preparing the electroactive Janus anodized aluminum oxide / polyvinylidene fluoride trifluoroethylene film according to claim 5, characterized in that: The voltage of the high-voltage electric field of the polarization treatment is 10-15 kV, and the time of the polarization treatment is 60-80 minutes.
Citation Information
Patent Citations
Electrified repair film material controllable in surface potential and preparation method thereof
CN109453431A
Surface amino modified piezoelectric polyvinylidene fluoride trifluoroethylene as well as preparation and application thereof
CN119019739A
Manufacturing method of unidirectional array carbon fiber sheet for reinforcing civil construction structure through the weaving of bind company
KR102155671B1
Electro-ultrasonic devices for nerve stimulation and treatment
US20160271427A1
Systems and methods for continuous production of fibrous materials and nanoparticles
US20230321570A1